The pandemic vocabulary in the Kazakh language - Sarseke, Г.Ә. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2023)
The article presents the results of the research on the vocabulary of Covid-19 in Kazakh. The purpose of this study is to determine the effect of the pandemic on the language and the expression of the pandemic vocabulary in the Kazakh language. The study provides a linguistic description of the pandemic lexicon and review on the specific linguistic corpora for the Covid-19. Based on Kazakh language data, words and phrases related to the pandemic were defined and their frequency of use was determined. Words with a high frequency of use in the first four months of 2020 were identified, and each of them was given a full linguistic description. This research employed the corpus-based analysis method. The data was collected from the newspaper "Egemen Kazakhstan" in Kazakh. The NVivo software was used to analyze the data, with the help of which the frequency of use of words and phrases related to the pandemic in the Kazakh language was calculated. The results of this study have shown that the vast majority of terms in the pandemic lexicon had acquired new meanings and their frequency has increased. A number of words in the pandemic lexicon used to be used in a general sense in the past, however, their use has increased in relation to the pandemic. The results of the pandemic vocabulary analysis showed that the most frequently used words in the first four months of 2020 were coronovirus, indet, quarantine, virus, pandemic and Covid-19.